2014
DOI: 10.1080/21642850.2013.869176
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of post-infectious chronic fatigue syndrome in adolescents

Abstract: This study focused on identifying risk factors for adolescent post-infectious chronic fatigue syndrome (CFS), utilizing a prospective, nested case-control longitudinal design in which over 300 teenagers with Infectious Mononucleosis (IM) were identified through primary care sites and followed. Baseline variables that were gathered several months following IM, included autonomic symptoms, days in bed since IM, perceived stress, stressful life events, family stress, difficulty functioning and attending school, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 51 publications
(68 reference statements)
1
28
0
Order By: Relevance
“…We found no unique mechanism(s) to explain the similarly reduced peakV O 2 in adolescents with chronic fatigue or chronic pain other than deconditioning, though we cannot exclude cortical/volitional influences perhaps prompted by altered perceptual responses to vigorous activity. matched controls (28); whereas another found that days spent in bed since the onset of infectious mononucleosis was a predictor of subsequent chronic fatigue (29). Similarly, there is overlap in clinical presentation of patients with chronic fatigue and chronic pain, fibromyalgia being the entity most studied (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…We found no unique mechanism(s) to explain the similarly reduced peakV O 2 in adolescents with chronic fatigue or chronic pain other than deconditioning, though we cannot exclude cortical/volitional influences perhaps prompted by altered perceptual responses to vigorous activity. matched controls (28); whereas another found that days spent in bed since the onset of infectious mononucleosis was a predictor of subsequent chronic fatigue (29). Similarly, there is overlap in clinical presentation of patients with chronic fatigue and chronic pain, fibromyalgia being the entity most studied (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing the same cohort, Katz et al [21] found that participants who developed ME/CFS post-infection demonstrated worse baseline autonomic symptoms than participants who fully recovered. From the same prospective study, Jason et al [22] found that baseline autonomic symptoms and days spent in bed from the infection, but not psychological measures, were the only significant predictors for the development of ME/CFS after infectious mononucleosis.…”
Section: Non-epidemic Post-viral Illnessmentioning
confidence: 98%
“…Research is needed to assess functioning during the recovery phase post-COVID-19. Such studies might include a full medical and psychiatric assessment, as well as use of standardized and validated measures of critical symptoms such as the severity of infection and autonomic functioning, which have been predictive of post-infection ME/CFS [4,21,22,26]. If possible, data from prospective designs, capturing characteristics of patients prior to infection might provide unique insights into predisposing factors helping to answer why certain individuals have more serious short-and long-term outcomes.…”
Section: Future Researchmentioning
confidence: 99%
“…A viral cause of ME/CFS has been long hypothesized, and there is evidence that both enteroviruses and herpesviruses may be involved in ME/CFS, at least in some cases. 12,13 Over the past 3 decades there has been a significant amount of research into the efficacy of antiviral drugs in the treatment of ME/CFS. These treatments generally include 2 different classes of antivirals, guanosine analogues, such as acyclovir and valacyclovir, and the immunomodulator rintatolimod.…”
Section: Antiviralsmentioning
confidence: 99%